Physiological demands of standing and wheelchair fencing in able-bodied fencers - Iglesias, X.; Rodriguez, F. A.; Tarrago, R.; Bottoms, L.; Vallejo, L.; Price, M. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The purpose of this study was to determine the cardiorespiratory demands of standing and wheelchair (seated) fencing in a group of able-bodied fencers during simulated competitive bouts. METHODS: Participants were ten male able-bodied fencers of regional level with previous training experience in wheelchair fencing. After a standardized warm-up, participants performed two series of simulated competitive épée bouts (5 and 15 touches) in a random order, either while standing or while sitting in a wheelchair. Expired gas was analyzed for oxygen consumption (V.O2) and respiratory exchange ratio (RER) and heart rate were continually monitored. Energy expenditure (EE) was subsequently calculated. RESULTS: V.O2, HR and EE peak responses were greater during standing than seated fencing (P<0.05). Mean V.O2 during all ST bouts (5- and 15-touch) was 43% greater than in wheelchair fencing (44.2±7.8 vs. 25.1±5.4 mL/kg/min). Mean HR during the standing 5- and 15-touch bouts was 91±20% and 84±7%, respectively, of that recorded during the seated bouts. HR, V.O2 and EE data also indicated that the 15-touch bouts were more physiologically demanding than the 5-touch bouts (P<0.01). The HR-V.O2 relationship was similar between both fencing modes. The duration of the 5- and 15-touch bouts were shorter for the seated than the standing bouts (P<0.01). CONCLUSIONS: The physiological demands of wheelchair fencing are lower than those for standing fencing. Furthermore, the physiology of 5 versus 15-touch bouts, similar to those undertaken in fencing competition, also differs.